1998
DOI: 10.1046/j.1365-8711.1998.02092.x
|View full text |Cite
|
Sign up to set email alerts
|

Submillimetre continuum images of the NGC 2024 star-forming ridge

Abstract: A B S T R A C TWe present 450-and 800-m images, made with the James Clerk Maxwell Telescope, of the NGC 2024 molecular ridge. The seven previously known compact cores, FIR1-7, have been detected, and FIR5 has been resolved into a compact object and an associated extended source to the east. The estimated masses of the dense cores vary between 1.6 and 5.1 M ᭪ per 14-arcsec beam, assuming a dust temperature of 30 K and a dust opacity of k 800 m ¼ 0:002 m 2 kg ¹1 . A spectral index map made from the 450-and 800-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 14 publications
7
54
1
Order By: Relevance
“…L 1157-mm region may thus be indicative of physical differences between the properties of the material toward the embedded source and those of the more extended region. This effect was already observed in other young embedded sources (Visser et al 1998;Johnstone & Bally 1999;Smith et al 2000;Beltrán et al 2002).…”
Section: Spectral Index Mapsupporting
confidence: 73%
“…L 1157-mm region may thus be indicative of physical differences between the properties of the material toward the embedded source and those of the more extended region. This effect was already observed in other young embedded sources (Visser et al 1998;Johnstone & Bally 1999;Smith et al 2000;Beltrán et al 2002).…”
Section: Spectral Index Mapsupporting
confidence: 73%
“…Observational studies have found evidence that β decreases as a result of grain growth at high densities (e.g., Goldsmith et al 1997;Visser et al 1998). More recently, Kwon et al (2009) found that β 1 for their sample of three Class 0 sources, resembling the values we found towards the Class 0 candidates IRAS 05405 and SMM 4.…”
Section: Dust Propertiesmentioning
confidence: 99%
“…Assuming that the dust opacity follows a power law with ( ) / and that the dust emission can be approximated by a blackbody at temperature T d , the dust emission is given by In practice, however, determining the dust temperature is complicated by the fact that the dust opacity power-law coefficient, , is poorly constrained and often varies with location and physical conditions (Goldsmith et al 1997;Visser et al 1998;Hogerheijde & Sandell 2000;Beuther et al 2004). In addition, the 450 and 850 m beam sizes at the JCMT are significantly different, and the 450 m beam is not well approximated by a single Gaussian function ( Hogerheijde & Sandell 2000 Assuming that ¼ 2 (Hildebrand 1983), the central dust temperature for each clump was estimated using the total flux in the convolved 850 and 450 m maps by inverting…”
Section: Clump Temperatures Derived From Submillimeter Colorsmentioning
confidence: 99%